2020
DOI: 10.3390/s20071850
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Cascade Laser-Based Multi-Gas Sensor for Ambient Air Monitoring

Abstract: A quantum cascade laser-based sensor for ambient air monitoring is presented and five gases, affecting the air quality, can be quantified. The light sources are selected to measure CO, NO, NO2, N2O and SO2. The footprint of the measurement setup is designed to fit in two standard 19” rack (48 cm × 65 cm) with 4 height units (18 cm) whereas one is holding the optical components and the other one contains the electronics and data processing unit. The concentrations of the individual analytes are measured using 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The emitted wavelength within ten wavenumbers is usually obtained by either changing the injected current or the temperature of the gain element. However, some typical analytes of interest are discretely distributed over the mid-infrared range and cannot be covered by a single QCL, therefore, multiple QCL lasers are also necessary. Although a QCL with an external cavity (EC-QCL) scheme can already cover a spectral range of >400 cm –1 and has been demonstrated for simultaneous detection of multiple atmospheric species and VOCs, it is rather unsuited for development of field-deployable compact gas sensors and still remains expensive. In comparison, near-infrared tunable distributed feedback (DFB) diode lasers were widely recognized as suitable light sources for developing optical spectroscopy gas sensors due to their long lifetime, compact size, low cost and low power consumption, wavelength tunability, high spectral quality, and reliability.…”
mentioning
confidence: 99%
“…The emitted wavelength within ten wavenumbers is usually obtained by either changing the injected current or the temperature of the gain element. However, some typical analytes of interest are discretely distributed over the mid-infrared range and cannot be covered by a single QCL, therefore, multiple QCL lasers are also necessary. Although a QCL with an external cavity (EC-QCL) scheme can already cover a spectral range of >400 cm –1 and has been demonstrated for simultaneous detection of multiple atmospheric species and VOCs, it is rather unsuited for development of field-deployable compact gas sensors and still remains expensive. In comparison, near-infrared tunable distributed feedback (DFB) diode lasers were widely recognized as suitable light sources for developing optical spectroscopy gas sensors due to their long lifetime, compact size, low cost and low power consumption, wavelength tunability, high spectral quality, and reliability.…”
mentioning
confidence: 99%
“…In this study, the solution to the data scarcity problem is to obtain the ideal absorption spectra of the gas mixtures under predefined experimental conditions from the HITRAN database and build the simulated data set by introducing systematic noises. This data augmentation strategy has been widely used in areas where information is scarce and has been proven to be practical [14]. Models trained on such simulated data sets will also perform well on experimental data.…”
Section: Data Setsmentioning
confidence: 99%
“…Due to the high brightness, QCL requires less integration time than FTIR and NIRS to operate in a higher signal-to-noise spectrum. Due to the high resolution of QCL, the analysis monitoring of gases [ 27 , 28 ] at extremely low concentrations with high selectivity is feasible, demonstrating the versatility of this instrument. Ostendorf et al [ 29 ] have shown the capabilities of QCL in diffuse reflectance mode for the analysis of food quality, detection of the presence of molds in peanuts, and remote detection of explosives with back reflection measurements.…”
Section: Introductionmentioning
confidence: 99%